An Indacenodithieno[3, 2‐b]thiophene‐Based Organic Dye for Solid‐State p‐Type Dye‐Sensitized Solar Cells. Issue 14 (29th May 2019) - Xu, Bo; Wrede, Sina; Curtze, Allison; Tian, Lei; Pati, Palas Baran; Kloo, Lars; Wu, Yiying; Tian, Haining
Abstract: An indacenodithieno[3, 2‐b]thiophene (IDTT) unit is used as a linker moiety to design a new p‐type dye—TIP—for solid‐state p‐type dye‐sensitized solar cells. Solar cells based on the TIP dye offered an efficiency of 0.18 % with an open‐circuit photovoltage of 550 mV and a short‐circuit photocurrent density of 0.86 mA cm −2, which is better than those of two reference dyes, PB6 and BH4. Charge lifetime experiments reveal that the IDTT linker‐based TIP dye significantly suppresses charge recombination losses in the devices. Abstract : Indacene proposal : An indacenodithieno[3, 2‐b]thiophene (IDTT) unit is used as a linker moiety to design a new p‐type dye—TIP—for solid‐state p‐type dye‐sensitized solar cells. Solar cells based on the TIP dye offered an efficiency of 0.18 % with an open‐circuit photovoltage of 550 mV and a short‐circuit photocurrent density of 0.86 mA cm −2 .